Integrasi Branding Dalam Interior Warunk Upnormal - andrianawati, aida; Yuniati, Arnanti Primiana (Waca Cipta Ruang, 2022)
The rapid growth of culinary tourism in Bandung has resulted in intense competition for cafe owners to survive in this industry. Especially with the emergence of conceptual cafes, business people need to overcome this situation by doing cafe interior branding. One of them is Warunk Upnormal. The concept of this cafe was originally adopted from a traditional Indonesian coffee shop (warkop). The aim of this research is to find out whether the application of interior branding at Warunk Upnormal is in accordance with Kim Kuhteubl's theory; which consists of clear vision aspects; unique story aspect; energi aspect. This research is a qualitative research using descriptive analytical method to see the integration between interior design and branding at Warung Upnormal. Methods of data collection include interviews, observation, photo documentation, and literature studies about café interior branding. Research finds that Warunk Upnormal has used Kuhteubl's interior branding theory. This can be seen from the sinage elements, spatial organization, furniture layout, type of music (clear vision); logo elements and interior concepts (unique story); elements of color, material, lighting, ventilation (energi). The implementation of these three aspects gives an interesting impression to visitors. Keywords: Interior, Interior Branding, Cafe Interior, Warunk Upnormal